LAYANAN KONSELING KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS VIII SMP NEGERI 20 PONTIANAK - Sisilawati, Sisilawati; Astuti, Indri; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLiving your daily life will not be separated from one's self-confidence in yourself, others, the environment and society. Self-confidence is a belief that someone has for himself so he feels able to do something. This confidence is one of the determinants of one's success both in the scope of the school and others.The problems in this study are (1) What is the stage of forming group counseling services to increase self-confidence of class VIII students in Pontianak State Junior High School, (2) What is the transition stage of group counseling services to increase the confidence of class VIII students in State Junior High Schools 20 Pontianak, (3) What is the stage of group counseling service activities to increase self-confidence of class VIII students in Pontianak State Junior High School, (4) What is the stage of termination of group counseling services to increase the confidence of class VIII students in Pontianak.The method used is descriptive method and the form of research is a form of relationship study. The population in this study were 35 students of Pontianak State Junior High School 20. This study uses a quantitative approach. Data collection techniques with questionnaires, while data analysis techniques use the percentage formula.Based on the results of this study indicate that the group counseling services to increase the confidence of class VIII students in the State Junior High School 20 Pontianak are the stages of formation, transition and termination with the category